Pengaruh Konten Bahasa Mandarin Terhadap Peningkatan Kosakata Mahasiswa Sastra Cina Universitas Brawijaya - Adinda Nabila Sitompul (Jurnal Asosiasi Program Studi Mandarin Indonesia (Jurnal APSMI), 2022)
Everyone knows that social media is one of the most important parts of mankind in this era. The existence of social media has many advantages for its users. One of the most obvious advantages is the presence of educational content on social media. Many people choose to create educational content so that it can be useful for many people. There are various kinds of educational content on social media, including content that teaches mandarin vocabulary. This study aims to see the effect of learning mandarin language on social media that improve Chinese Literature Students of Brawijaya University on their mandarin vocabulary skills. This study uses a quantitative method with the process of collecting the results of questionnaire data and direct interviews with Chinese Literature Students Brawijaya University. Participants are students of Chinese Literature BrawijayaUniversity batch 2019 with total 60 students. The results of this study can show the effect of Chinese Literature Students of Brawijaya University mandarin vocabulary ability before and after they use Chinese learning content on social media as a new learning tools.